2018
DOI: 10.1007/s00394-018-1626-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ewe’s milk yogurt (whole and semi-skimmed) and cow’s milk yogurt on inflammation markers and gut microbiota of subjects with borderline-high plasma cholesterol levels: a crossover study

Abstract: Ewe's yogurt effects on inflammatory markers and microbiota were not different from those after cow's yogurt, but the attenuation of some inflammatory biomarkers with ewe's whole-milk yogurt in subjects with the highest TC/HDL-c deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…On the other hand, one of the main foci in probiotic-based studies is the evaluation of Lactobacilli changes, with evidence showing either positive [11,24,52] or neutral effects [15,16,18]. Lactobacillus species account for a very small proportion in the gut microbiota composition of our subjects, agreeing to previous works suggesting that Lactobacilli levels are very low in the colon and predominate in the small intestine [4,53]; thus, it is not surprising the lack of findings related to both probiotics containing fermented milks and yogurt intake in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, one of the main foci in probiotic-based studies is the evaluation of Lactobacilli changes, with evidence showing either positive [11,24,52] or neutral effects [15,16,18]. Lactobacillus species account for a very small proportion in the gut microbiota composition of our subjects, agreeing to previous works suggesting that Lactobacilli levels are very low in the colon and predominate in the small intestine [4,53]; thus, it is not surprising the lack of findings related to both probiotics containing fermented milks and yogurt intake in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, while several studies have failed to show a good recovery of the yogurt starters in feces of healthy adults [9,10,11], others have shown the opposite [12,13]; differences which might be explained by the type of strain, the dose of ingested cells, or the different methodologies employed to assess the gut microbiota composition [14]. Despite these controversies, the most common effect observed after yogurt intake in healthy adults is an unaltered gut microbiota [9,15,16]; only one study has evidenced increased Lactobacillus levels [11], so the use of the term “probiotic” for yogurt starters based on their ability to beneficially affect the gut microbiota composition remains unclear. In this sense, the addition of probiotic strains along with yogurt bacteria during fermentation could facilitate a better colonization of the host intestinal environment [17].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the intake of whole ewe’s milk yogurt over 5 weeks, which differs from semi-skimmed (ES) ewe’s yogurt and from cow’s milk yogurt in fat quality, decreased Blautia-coccoides only in women of this group when compared to the period of ES yogurt intake. In addition, cow’s milk yogurt increased C. leptum compared to ES only in subjects of the medium- and low-cholesterol/HDL–cho ratio [ 91 ].…”
Section: Dietmentioning
confidence: 99%
“…It seems thatC increased cortisol levels compared to ewe yogurt (ES) in woman with normal cardiovascular risk. Many studies related CLA intake with a decrease of IgE, TNF-α and IL-1β [47,49], however results previously published by the authors [21]showed that the consumption of ewe yogurt did not affect TNF-α differentially than cow yogurt consumption.…”
Section: Cortisol Determinationmentioning
confidence: 91%
“…One stool sample and a 72-h dietary register were also collected at these time points. DIAL software was used to analyse the nutrients composition of volunteer's habitual diet, excluding the experimental products intake [21]. Plasma of the different patients was separated from blood samples, stored at -80°C, and used for the cortisol determination in all patients at the start and end of each intervention period.…”
Section: Clinical Assaymentioning
confidence: 99%